Causality nexus of exports, FDI and economic growth of the ASEAN5 economies: evidence from panel data analysis - Ahmad, F. (Routledge, 2018)
This paper analyzes the causal relationships between exports, FDI and economic growth among the ASEAN5 countries. We have used a three-stage procedure based on unit root, co-integration and causality tests applied to the panel data from 1981 to 2013. The results reveal that there is a bi-directional causal relationship between FDI and growth in the long run, while there is a unidirectional causal relationship from FDI to exports in the short run. Our results also confirm that the export-led growth (ELG) and FDI-led growth hypotheses hold true in the long and short run. To reinforce the FDI inflows, authorities should continue the progressive reduction of barriers, and increase the sophistication of quality exports to compete in the global market. This paper is the first of its kind to analyze the role of both FDI and exports in the ASEAN5 economies using panel analysis. Â© 2018, Â© 2018 Informa UK Limited, trading as Taylor & Francis Group.